Leadership in Action : the Essence of Developmental Coaching - Kirkland, Wayne Hart. Karen (Center for Creative Leadership, 2001)
If you sign on with an executive coach to help you improve your leadership, your coach will direct you through a series of developmental steps. But it's not all up to the coach. Without your commitment to each step, you won't get far.